From the Northern Hajar Foothills to the Batinah Coast: a geoarchaeological survey at Saham and Dahwa (Northern Oman) - Engel, Max; Zander, Anja; Kehl, Martin; Feulner, Gary R.; Douglas, Khaled A.; Ğawharī, Nāṣir Saʻīd ʻAlī al-; Al-Hinai, Nasser Hamad; Brückner, Helmut (Open Quaternary, 2024)
Abstract: This geoarchaeological survey was dedicated to (i) the Umm an-Nar (2700–2000 BCE) settlement site of Dahwa and surrounding areas in the foothills of the Hajar Mountains as well as (ii) the coastal area near Saham on the Batinah coastal plain in northern Oman, the latter without focus on a specific cultural epoch. Stratigraphic sections from the proximal coastal plain provide insights into highly dynamic episodic sedimentation patterns with thick units of variable grain sizes and sorting. In one of the stratigraphic profiles in the town of Saham, a small anthropogenic pit or channel was found, interpreted as a pit hearth used by the Samad culture (300 BCE–100/200 CE) based on granulometry, thin-section analysis, clustered macro-charcoals, amorphous organic remains, as well as luminescence and 14C dating. Our coincidental discovery of this site indicates that there might be abundant traces of the Samad culture buried in the thick alluvium, from a period of hydrologically favourable conditions c. 50–300 CE. The Umm an-Nar dating of the Dahwa archaeological site in the foothills of the Hajar Mountains was confirmed for the first time by luminescence dating, although the low dose rate and high scatter of equivalent doses pose substantial challenges to the regional application of this method.